DOMINASI PERADABAN BARAT DALAM PENDIDIKAN ISLAM - Hasanuddin Hasanuddin (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2008)
The downfall of educational and Islamic civilization after the 13th century was recognized by the stagnation of Islamic thinking towards the 18th century and the fall of Baghdad and Granada as the centre of Islamic education and culture. After the European obtained the philosophy and science from Muslim, the Europe was gradually stronger in science and technology in parti-cular. On the other hand, the Muslim continued to decline as they disregarded the philosophy. Hence, the Muslim may develop, only, if they learn philosophy, science, and technology.